The Mayor of Casterbridge - Hardy, Thomas, 1840-1928 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Mayor of Casterbridge" by Thomas Hardy is a novel published in 1886. In a drunken moment at a country fair, young hay-trusser Michael Henchard auctions off his wife and infant daughter to a stranger. Years later, filled with remorse and now a successful mayor, Henchard attempts to rebuild his life when his past returns unexpectedly. This tale follows his struggles with ambition, rivalry, and the consequences of his fateful decision in rural England. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Mayor_of_Casterbridge
Release date is 2006-03-11
John Hamm and David Widger
Keywords: Psychological fiction; Fathers and daughters -- Fiction; Men -- England -- Fiction; Wessex (England) -- Fiction; Runaway husbands -- Fiction; Atonement -- Fiction; Mayors -- Fiction